PERTANGGUNGAN HUKUM ATAS PENCEMARAN LINGKUNGAN AKIBAT TUMPAHAN MINYAK PADA KILANG DI KABUPATEN CILACAP DALAM PERSPEKTIF HUKUM LINGKUP - Bangkit Wahyu Indra Gunawan; Eti Mul Erowati; Wiwin Muchtar Wiyono; Elly Kritiani Purwendah (Program Studi Ilmu Hukum, Jurusan Hukum dan Kewarganegaraan, Fakultas Hukum dan Ilmu Sosial, Universitas Pendidikan Ganesha, 2026)
This study examines legal liability for environmental pollution caused by oil spills at oil refinery facilities in Cilacap Regency from the perspective of environmental law. Oil spills, as a form of environmental pollution resulting from oil industry activities, have significant impacts on ecosystems, public health, and environmental sustainability. This research employs a normative juridical method with statutory and conceptual approaches to analyze legal regulations governing corporate liability for environmental pollution. The findings indicate that legal liability for oil spills can be imposed through administrative, civil, and criminal mechanisms as regulated under Indonesian environmental law. In addition, the principle of strict liability may be applied to activities that pose high environmental risks, including oil refinery operations. However, in practice, law enforcement still faces challenges in terms of evidence, supervision, and the effectiveness of sanction implementation. Therefore, strengthening regulations and optimizing the role of government in environmental supervision are necessary to ensure environmental protection and sustainability.